Factors-Factors Influencing The Behavior of Preventing The Transmission of Covid-19 Students - Annisa Sekar Sari; Evi Widowati (Universitas Negeri Semarang, 2023)
The Covid-19 outbreak is an infectious disease caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV by-2). Corona virus has many variants, omicron is the variant that has the highest transmission rate. Students are part of the community who need to participate in preventing Covid-19 in the form of behavior to prevent transmission of Covid-19. The purpose of this study was to determine the factors that influence students' behavior to prevent the transmission of Covid-19. This type of research is quantitative with a cross-sectional study approach . The sample is set at 175 respondents with probability sampling technique . The instrument used is a questionnaire. Data were analyzed using the Chi-Square statistical test and Multiple Logistic Regression. The results showed that the variables female gender (P 0.05; CI = 3.276), good knowledge (P 0.05; CI = 7.369), and mother's education level Masters (P 0.05; CI = 1.446) had the greatest influence of other variables. Suggestions need to increase student awareness to implement the Covid-19 health protocol as well as preventive support from parents, especially mothers in the context of preventing the transmission of Covid-19